Effects of combined diet and physical activity on glycemic control and body composition in male recreational athletes with type 2 diabetes mellitus - Chouk, Kayri; Triki, Raoua; Dergaa, Ismail; Ceylan, Halil İbrahim; Bougrine, Houda; Raul-Ioan, Muntean; Ben Abderrahman, Abderraouf (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is associated with metabolic and cardiovascular complications. While physical activity and dietary modifications are established interventions, their combined effects in active male populations remain underexplored.ObjectiveTo assess the effects of a 12-week therapeutic diet and/or physical activity program on body composition and biochemical parameters in male recreational athletes with T2DM.MethodsThirty-six male recreational athletes (aged 30–45 years) with T2DM were randomly assigned to: Physical Activity (PA), Nutritional Regimen (NR), Combined PA and NR (PA+NR), or Control (CG) groups. Body composition (body mass, body fat percentage, muscle mass) and biochemical markers (FBS, HbA1c, LDL-C, HDL-C, HOMA-IR) were measured at baseline, midpoint, and intervention end.ResultsThe PA+NR group showed significant improvements in body composition: reduced body mass (p<0.05, ES=0.29), reduced body fat percentage (p<0.05, ES=0.31), and increased muscle mass (p<0.05, ES=0.35). This group also demonstrated significant improvements in biochemical markers: reduced FBS (p<0.05, ES=0.17), HbA1c (p<0.05, ES=0.23), LDL-C (p<0.05, ES=0.17), and HOMA-IR (p<0.05, ES=0.39), with increased HDL-C (p<0.05, ES=0.29). The PA group showed only HbA1c reductions, while the NR group primarily improved lipid profiles. No significant changes occurred in the control group.ConclusionA combined therapeutic diet and physical activity program effectively improved body composition and biochemical parameters in recreational athletes with T2DM. This combined approach could be recommended as an integral strategy for diabetes management in physically active individuals.